The Role of NGOs in Promoting Social Justice for Indigenous Communities in Indonesia - Amelia, Anita Reski (Journal Social Humanity Perspective, 2024)
This observe examines the pivotal role of NGOs in promoting social justice for indigenous groups in Indonesia, specializing in key areas such as land rights, schooling, healthcare, and community empowerment. The findings screen giant advancements facilitated by means of NGO initiatives, including a 70% reputation fee of land titles, 80% faculty enrollment, 70% literacy, and eighty% get admission to to healthcare services. However, demanding situations remain, as 30% still lack diagnosed land titles, 20% of children are unenrolled, 30% are illiterate, and 20% lack get right of entry to to healthcare. Community empowerment efforts have brought about 65% participation in selection-making and 60% get entry to to monetary opportunities, though 35% stay excluded from governance and 40% face economic difficulties. These outcomes underscore the essential impact of NGOs while highlighting the want for ongoing efforts to address ultimate gaps and make sure sustainable and equitable development for all indigenous communities.